Efektivitas Penerapan Strategi Pemerintahan Indonesia dalam Menghadapi Regulasi Renewable Energy Directive II (RED II) DI UNI Eropa Tahun 2018-2020 - Dini Tiara Sasmi (UIR Press, 2021)
This paper examines the effectiveness of the Indonesian Government's strategy in dealing with regulations that limit the consumption of palm oil in Europe called the Renewable Energy Directive II (RED II). This prohibition was followed by a decrease in palm oil exports to Europe which made the Indonesian government try to carry out a countering anti-palm oil campaign (CAPOC) led directly by the Indonesian Ministry of Foreign Affairs. Some of the efforts that have been made include improving downstream sector governance, expanding Indonesia's palm oil exports destination countries besides Europe, such as America, Asia, and Africa, revitalizing and rejuvenating palm oil plantations, conducting intergovernmental diplomacy (G to G) between Indonesia and countries within the European Union, upgrading the B-20 program to B-30 to B-100 and finally CAPOC. The results of the study show that from several strategies carried out by the government, improving downstream sector governance, expanding the scope of Indonesian palm oil exports, and increasing the B-20 program to B-30 are the most effective strategies in dealing with RED II in Europe. This paper uses a qualitative method used secondary data and descriptive analysis techniques in explaining the existing data. This paper aims to describe the effectiveness of the strategies that have been carried out by the Government of Indonesia in dealing with RED II regulations in the European Union.